Keputusan Pembelian Generasi Z Atas Ponsel Pintar: Peran Brand Consciousness, Price Consciousness, dan Gender - Bramantio, Dhean Putera; Wulani, Fenika; Kristyanto, Visi Saujaningati (BIP's JURNAL BISNIS PERSPEKTIF, 2025)
Smartphones have become a significant element of Generation Z's life as they are heavily reliant on technology. Nowadays, Generation Z tends to be involved in making purchasing decisions for electronic products. As a result, it is critical to understand better how they make smartphone purchasing decisions. This study aims to analyze the influence of brand and price consciousness on Generation Z's smartphone purchasing decisions. This study also tested the role of gender in the relationship between brand and price consciousness in purchasing decisions. This research design used a survey by distributing Google Form questionnaires to respondents with a Generation Z profile in Surabaya Raya (Surabaya, Sidoarjo, and Gresik). One hundred eleven responses were collected and analyzed using SmartPLS 4.0 software to perform Partial Least Square-Structural Equation Modelling (PLS-SEM). The test results show that brand consciousness and price consciousness can enhance purchase decisions. Testing with multigroup analysis (MGA) shows that the influence of brand consciousness on purchasing decisions depends on gender. However, on the contrary, the influence of price consciousness on purchasing decisions does not depend on the gender of the smartphone consumers who participated as respondents in this study. The findings of this study provide an understanding of the importance of organizations comprehending the profile of this new generation and their expectations regarding smartphone products.